A Survey on Simultaneous Wireless Information and Power Transfer; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Ponnimbaduge Perera T. D. Tarindu Dilshan; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; De S.; Ivanov M. A. Maksim Anatoljevich (2017, 2017)
Title screen